2020
DOI: 10.1101/2020.11.25.20238683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Isolated Systolic Hypertension among People with Diabetes in Indonesia

Abstract: The present study aimed to explore the prevalence of isolated systolic hypertension (ISH) and its risk factors among diabetes mellitus (DM) subjects in the community setting study in Indonesia. This cross-sectional study extracted secondary data from basic health survey (Riset Kesehatan Dasar; RISKESDAS) conducted in 2018. DM subjects were defined based on fasting blood glucose level ≥ 126 mg/dL or 2 hours postprandial and random blood glucose level ≥ 200 mg/dL or previously had been diagnosed by a doctor; whi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The detailed study protocol was published in the official RISKESDAS report 25 and other publications. 26,27 In total, respondents in the RISKESDAS were 1,017,290 subjects from 416 districts and 98 cities in 34 provinces.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed study protocol was published in the official RISKESDAS report 25 and other publications. 26,27 In total, respondents in the RISKESDAS were 1,017,290 subjects from 416 districts and 98 cities in 34 provinces.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on stroke risk factors have been widely reported, especially the incidence of stroke in subjects with diabetes mellitus (7) and hypertension (8). However, limited studies were reported on people with isolated systolic hypertension (ISH).…”
Section: Introductionmentioning
confidence: 99%